Faktor Predisposisi dan Pendukung Tes HIV pada Wanita Hamil - Rossalya, Monica Ayu; Ernawaty, Ernawaty; Widati, Sri; Dick-Sagoe, Christopher (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze predisposing and supporting factors in the use of HIV testing in pregnant women. The method used is a literature review using the PRISMA checklist and searching for articles from 2015 to 2020, utilizing five databases: Cambridge eJournal, Scopus, Science Direct, Proquest, and Google Scholar. The results obtained 16 articles that met the inclusion criteria from 2036 articles in this study. In conclusion, most of the use of HIV testing is influenced by age factors, education level, perceptions of HIV testing, health promotion, human resources, infrastructure, and facilities, which have a significant impact on the awareness, willingness, and ability of pregnant women to undergo HIV testing. Keywords: Supporting Factors, Predisposing Factors, HIV Testing